Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.9734/ajarr/2019/v6i230147
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting E-commerce Adoption of Small and Medium Enterprises in Sri Lanka: Evidence from Retail Sector

Abstract: Purpose: There is a resistance in the adoption of e-commerce in certain parts of the world even though most successful businesses in the world has successfully adopted e-commerce to their businesses gained an increasing success. The study aims to find the crucial factors affecting to the adoption of e-commerce by using the evidence of retail sector in Sri Lanka as a developing nation. Methods: The targeted population for the study was the retail sector registered as Small and Medium Enterprises in Colomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 8 publications
1
12
0
4
Order By: Relevance
“…The hypotheses which are not supported with e-commerce usage are IT infrastructure and external pressure with 01.23 p-values and 0.43, respectively. The possible reason for the insignificant relation of IT infrastructure with e-commerce usage is that increased technology infrastructure various complexed processes introduced like payment methods, financial transactions (Govinnage & Sachitra, 2019). Moreover, It is surprising that even in SMEs, the owner and CEO behave neutrally in terms of external pressure impact on e-commerce adoption (Lip-Sam & Hock-Eam, 2011).…”
Section: Hypotheses Testing Resultsmentioning
confidence: 99%
“…The hypotheses which are not supported with e-commerce usage are IT infrastructure and external pressure with 01.23 p-values and 0.43, respectively. The possible reason for the insignificant relation of IT infrastructure with e-commerce usage is that increased technology infrastructure various complexed processes introduced like payment methods, financial transactions (Govinnage & Sachitra, 2019). Moreover, It is surprising that even in SMEs, the owner and CEO behave neutrally in terms of external pressure impact on e-commerce adoption (Lip-Sam & Hock-Eam, 2011).…”
Section: Hypotheses Testing Resultsmentioning
confidence: 99%
“…However, in technology adoption literature, government support is an initial endeavor in both developed and underdeveloped regions of the globe. Based on research by Govinnage and Sachitra (2019), results showed that government support has a positive effect on SMEs in Sri Lanka. However, the government of Pakistan has developed policies for a large organization but is less focused on SMEs; thus, the influence of government support on performance is addressed in the following hypothesis:…”
Section: Government Support Relationship With the Use Of E-commercementioning
confidence: 99%
“…Coherently, this may affect SMEs in their competitiveness and eventual survival of these countries. While focusing on these factors may be useful for comparing SMEs in developing and developed countries, the reliance of SMEs on e-commerce in developing countries differs significantly from that of developed countries, and the results cannot be generalised (Govinnage & Sachitra, 2019).…”
Section: The Relationship Between the Frequency Of Technology Use And...mentioning
confidence: 99%